Best practices for equity research analysts : essentials for buy-side and sell-side analysts - Valentine, James J. (New York : McGraw-Hill, 2011)
The book covers the five primary areas of the equity research analyst's role: identifying and monitoring critical factors; creating and updating financial forecasts; deriving price targets or a range of targets; making stock recommendations; communicating stock ideas.
Includes bibliographical references and index.
rua 24/02/17
Loans.
Keywords: Investment advisors; Investment analysis